Governance of Emissions Trading Systems - Partnership for Market Readiness; International Carbon Action Partnership (World Bank, Washington, DC, 2022)
Emissions trading continues to expand as a flexible policy response to climate change. Its implementation raises complex governance challenges, however, and calls for robust institutional, regulatory and procedural frameworks. Unlike aspects of technical design and implementation, the governance of emissions trading systems (ETSs) has found less extensive treatment in the available knowledge base. However, existing systems offer valuable insights into the successful governance of emissions trading from the initial establishment and routine operation of an ETS to the review of its performance and the management of change. This report draws on such experiences to provide guidance on the governance of an ETS across all stages of its evolution.